Extracorporeal haemoadsorption: does the evidence support its routine use in critical care? - Supady, Alexander; Brodie, Daniel; Wengenmayer, Tobias (The lancet. Respiratory medicine, 2022)
Extracorporeal haemoadsorption is increasingly being used for the removal of endotoxin or inflammatory cytokines in patients with septic shock or other severe inflammatory states. A reduction in excessively high levels of inflammatory mediators—and mitigation of the devastating clinical impact of severe inflammation—might be a sound rationale for extracorporeal haemoadsorption in critical care, but the evidence for beneficial effects is uncertain. Few randomised controlled trials have been undertaken, and they have not provided reliable evidence for routine use in clinical practice. No study has shown a survival benefit, and only a few studies have shown a significant effect on patients' blood cytokine concentrations. Nonetheless, some clinicians have encouraged the use of haemoadsorption devices, largely on the basis of incomplete data or contentious interpretations of the available data. Further research is required, particularly well designed, prospective clinical trials assessing relevant patient-centred outcomes, including mortality, before widespread adoption of this technology can be recommended.